Provision of a course guide as a learning tool for fourth year medical clerks - Ng, Rodolfo C.
Adult learners like medical students are considered responsible, autonomous, experiential, and reflective in their pursuit for learning. They want immediate application from what they have learned and seek transfer of learning from theory to practice. This contention, however, is not always true because problems encountered at Angeles University School of Medicine during pediatric clerkship include failure to track and monitor their learning tasks and consistent low passing marks in comprehensive examinations for the past 6 years. These prompted the department to develop a course guide that is uniquely both a study and a training guide to serve as a solution to these pressing problems. The aims of this study are 1) to determine the perceived learning experiences from the two comparative study groups rotating at the Department of Pediatrics; one group provided with a course guide and the other did not; 2) to determine the differences of the two groups in their cognitive performance based on the results of written comprehensive examinations after their rotations, and 3) to determine the differences of the two groups in their clinical competency performance based on residents' rating, clinical learning tasks appraisal and their perceived level of competency after their rotations. A causal-comparative research design was conducted involving 14 14th year medical students as the "control" group and 12 students as the "exposed" group with the innovation. Focus group discussion showed a favorable learning experience from the group with the course guide. Both groups did not differ in their responses for their training and learning activities and they generally agreed that their teaching faculty were all right. Both groups, however, gave varied responses as to their personal interests of subjects to learn, factors that facilitated and hindered their learning. The group with the course guide showed improvement in their cognitive performance based on the results of the comprehensive examination. Students who used the course guide had relatively better clinical performance in various aspects based on the residents' evaluation. However, their clinical learning appraisals and perceived level of competency compared to their counterpart were varied in ambulatory, hospital and nursery setting. The "exposed" group generally found the course guide to be acceptable based on their overall strong agreement to the statements. To date, provision of a course guide indeed showed encouraging results that it can be developed and implemented as an added teaching and learning material for the 4th year medical students in their pediatric clerkship rotation.